Existentialism, Authenticity and Modern Debates Over Incapable Individuals - Zhou, Runyang (Transactions on Social Science, Education and Humanities Research, 2024)
This study offers a comprehensive explanation of Sartre’s existentialist vision of man’s true nature and the concept of freedom in terms of the cognitive categories, moral responsibility, and intelligibility of behaviour of the modern individual. Specifically, the study focuses on the modern individual. It attempts to present some dilemmas about freedom and individual behaviour in the form of a history of ideas by echoing each other with some intellectual traditions and currents of modernity that are closely related to one another. For the purpose of concentrating the work of this study, a number of comparative approaches to the history of philosophy have been selected. These approaches, in particular those that are founded on action analysis and social contextualization, have been selected. By utilising these comparisons, the purpose of this study is to attempt to uncover some theoretical conundrums concerning freedom that are associated with the existentialist or humanist system of thought, as well as to propose theoretical reflections that correspond to these concerns. The clues that are sorted out in this article will be of great assistance in the future when attempts are made to be successful in completing the numerous tasks of theoretical advancement work that fall under the concept of freedom in traditional continental philosophy.